ORGANIZATION OF EDUCATIONAL COLLABORATION IN INTERNET - Zavadsky, A.B.; Zavadsky, I.O. (Journal of Information Technologies in Education (ITE), 2010)
The purpose and usage methodology of network collaborative learning software are discussed. The Internet collaborative learning system “Informatics” is described.